Perancangan Sistem Mesin Layanan Mandiri di Kantor Bapenda Medan - Muhammad Aldo Faturrahman; Armansyah Putra Siregar; Dio Arif Hanafi Harianja (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET), 2025)
Information systems are essential to support work processes and public services.One type of information technology widely used in government institutions, such as the Regional Revenue Agency of Medan City, is the management of official correspondence.Every organization or institution has various tools to convey information to others, one of which is through letters.The disposition of letters is a public service that needs improvement at the Regional Revenue Agency of Medan City.This study aims to design a self-service application that facilitates the management of letter dispositions, thereby improving the efficiency of administrative services.The research employs the waterfall method, which includes the stages of requirements analysis, design, implementation, and testing.The result of this research is a prototype application that enables digital management of letter dispositions, equipped with features that simplify tracking and managing letters for both administrators and users.These findings are expected to serve as a foundation for further development of digital administrative services in other government institutions.